PWE-027 HALO radiofrequency ablation for squamous high grade dysplasia and early squamous cell carcinoma: outcomes form the UK HALO radiofrequency ablation registry. (28th May 2012) - Haidry, R J; Dunn, J; Banks, M; Gupta, A; Butt, M A; Smart, H; Bhandari, P; Smith, L-A; Willert, R; Fullarton, G; Di Pietro, M; Penman, I; et al.
Abstract : Introduction: Squamous Cell Cancer (SCC) of the oesophagus has a poor prognosis with 5-year survival at 10%. Squamous high grade dysplasia (HGD) is the precursor lesion to SCC. Risk of progression to SCC with Squamous HGD can be 65% at 5 years. Radiofrequency ablation (RFA) is a minimally invasive ablation technique with proven efficacy for early neoplasia in Barrett's Oesophagus. Methods: Prospective multicenter registry of patients undergoing RFA for Squamous HGD and early carcinoma in situ (CIS) from eight UK centers. Nodular lesions were removed by endoscopic mucosal resection before RFA. Treatment consisted of a single ablation at 12 J/cm 2 . Patients were followed-up 3 monthly and repeat biopsies taken. Those with residual dysplasia underwent RFA 3 months later until 12 months where they were assessed for treatment success or failure. Results: 25 patients have undergone ablation for squamous HGD/CIS. We report on 17 patients to have completed protocol. Mean length of dysplastic epithelium ablated was 5 cm (1–14). Mean time to protocol completion was 8.7 months. CR-HGD was seen in 59% of patients and CR-D in 47% at end of protocol biopsy with mean of 1.4 RFA treatments (1–3). All those with successful outcomes remain free of dysplasia at most recent biopsy, median follow-up 10.6 months (2–36) from first treatment. At protocol completion, six of 17 patients (35%) had progressed to invasive cancer and referred for surgery or chemo-radiotherapy. Three patients (18%) required dilatations for oesophageal structuring after first treatment. Two of these patients have required serial dilatations thereafter with an average of four dilatations per patient. Conclusion: Squamous HGD and CIS are very aggressive pathologies as evidenced by the fact a third of patients progressed to invasive disease despite RFA. The role of RFA in these patients remains unclear. In our series 47% of patients responded to RFA & have reassuringly remained free of dysplasia at last follow-up. These figures are lower than limited published data to date but in our series an emphasis was placed on restaging carefully after each treatment to assess for progression. As our experience grows with confidence in identifying these lesions more accurately and increasing the frequency and number of ablations administered over the protocol period, dysplasia reversal rates will be expected to increase. Competing interests: None declared.